A novel microRNA miR-1165-3p as a potential diagnostic biomarker for allergic asthma. (2nd January 2019) - Wu, Chaojie; Xu, Kun; Wang, Zhengxia; Chen, Zhongqi; Sun, Zhixiao; Yu, Wenqing; Ji, Ningfei; Huang, Mao; Zhang, Mingshun
Abstract: Context: A further examination of a novel miRNA, miR-1165-3p as a biomarker for asthma, which was previously implicated in helper T cells (Th2) in a murine asthma model. Objective: To determine whether serum miR-1165-3p can serve as a potential diagnostic biomarker for allergic asthma. Methods: Serum miR-1165-3p was quantified via quantitative real-time PCR (qRT-PCR) in asthmatic and control samples. Serum miR-1165-3p levels were compared between groups and the clinical diagnostic abilities of miR-1165-3p were evaluated. The analyses utilized included a student's t test, one-way ANOVA, and the generation of receiver operating characteristic (ROC) curves. Results: Serum miRNA-1165-3p levels were significantly elevated in asthmatics when compared to the healthy controls. Furthermore, the sensitivity and specificity of serum miR-1165-3p were found to be 83% and 68.2%. Additionally, serum miR-1165-3p levels were also found to be significantly elevated in patients with allergic rhinitis (AR) or allergic bronchopulmonary aspergillosis (ABPA). Conclusions: This study showed that serum miR-1165-3p can potentially be utilized as a noninvasive biomarker that is able to aid in the diagnosis and characterization of allergic asthma.